Homonymous Horizontal Sectoranopia Caused by an Occipital Lobe Infarct - Preble, Janine M. (Neuroophthalmology, 2019)
Homonymous horizontal sectoranopia is a rare visual field defect that characteristically occurs after damage to the lateral geniculate nucleus (LGN). While there are many reports of homonymous horizontal sectoranopia resulting from LGN damage, there are very few reports of homonymous horizontal sectoranopia resulting from damage to other areas of the brain. We present a unique case of a patient with a homonymous horizontal sectoranopia with an occipital lobe infarct. Visual field and radiologic findings are presented. To our knowledge, this is one of the few reported cases of homonymous horizontal sectoranopia resulting from an infarct to the occipital lobe.